Rapid implementation of open-access pandemic education for global frontline healthcare workers - Jacqueline Christianson; Erica Frank; Stacen Keating; Susan Boyer; Miriam Chickering (BMC Research Notes)
Abstract Background The recent global pandemic posed extraordinary challenges for healthcare systems. Frontline healthcare workers required focused, immediate, practical, evidence-based instruction on optimal patient care modalities as knowledge evolved around disease management. Objective This course was designed to provide knowledge to protect healthcare workers; combat disease spread; and improve patient outcomes. Methods A team of global healthcare workers responded by rapidly creating a competency-based online course. To promote transcultural applicability, the course was developed by an international team of more than 45 educators from over 20 countries. Course delivery included a built-in language translation tool, routine updates, and several innovative course design elements. User feedback was collected to determine efficacy of course content, structure, unique delivery elements, and delivery options. Results An initial population of online learners (n = 147) living in 23 different countries and representing 22 languages completed the course and participated in post-course surveys. An additional population of learners (n = 505) attended an in-person offering of course materials. Course participants gave positive feedback and several requested additional courses in similar formats. Conclusion Global open access education courses may provide needed resources to empower healthcare professionals during health crises. Responsive course design can accommodate diverse learner resources and transcultural applicability.